Calcitonin: characterisation and expression in a teleost fish, Fugu rubripes - Clark, Melody (2018)
The present report describes the structure and expression of the calcitonin gene in Fugu rubripes. It is composed of 4 exons and 3 introns. Splicing of exons 1, 2 and 3 generates the calcitonin pre-proprotein, while splicing of exons 1, 2 and 4 generates calcitonin gene-related protein (CGRP). Exons 1 and 2 encoding the signal sequence and the N-terminal peptide are common in both the gene products and this gene organisation has been conserved in human, rat, chicken and salmon. The gene environment around calcitonin in Fugu has been poorly conserved when compared with human, apart from a small gene cluster. The calcitonin gene in Fugu has a widespread tissue distribution but it is most highly expressed in the brain. The abundance of gene expression in the ultimobranchial gland and the pituitary indicates that these are important sites of production and that the peptide is probably secreted into the circulation and/or acts as a paracrine or autocrine controlling factor. Whilst the function of calcitonin in fish is still largely unknown, the distribution described here suggests that one of the potential functions may be as a neuropeptide.